2012
DOI: 10.1177/0194599812460985
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Modified Brief Fatigue Inventory in Head and Neck Cancer Patients

Abstract: The MBFI is a reliable and valid tool for measuring fatigue levels in head and neck cancer patients. In the context of initial assessment or posttreatment trending, this brief survey can be rapidly administered, providing valuable objective data on a very common and potentially debilitating symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The scoring system of the BFI was modified (MBFI) from the original 0-10 point numeric scale to a 1-7 point scale [68]. The same 9 items were retained and validated in patients with head and neck cancer [19].…”
Section: Section Two: Scale Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring system of the BFI was modified (MBFI) from the original 0-10 point numeric scale to a 1-7 point scale [68]. The same 9 items were retained and validated in patients with head and neck cancer [19].…”
Section: Section Two: Scale Characteristicsmentioning
confidence: 99%
“…The same 9 items were retained and validated in patients with head and neck cancer [19]. Two validation studies of the MBFI, showed good internal consistency of the subscales (coefficient alpha: 0.93-0.86) [21,68]. In people with cancer, the MBFI meets the quality assessment criteria for content, criterion and construct validity along with reliability and internal consistency.…”
Section: Section Two: Scale Characteristicsmentioning
confidence: 99%
“…The definition typically involves the feeling of fatigue not relieved by rest, or how much fatigue impacts ones QoL on a daily basis, and can be scored using the CTCAE scale or using validated patient questionnaire instruments. 60,61…”
Section: Resultsmentioning
confidence: 99%
“…Post treatment fatigue is a key issue and could be a barrier to exercise recovery. In future surveys it would be possible to measure patients' perception of fatigue using the Modified Brief Fatigue Inventory (MBFI) 14 which was designed to measure intensity and frequency of fatigue specifically in HNC patients. Interestingly, predictors of increased MBFI score included American Society of Anesthesiologists (comorbidity), cancer stage and adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, predictors of increased MBFI score included American Society of Anesthesiologists (comorbidity), cancer stage and adjuvant radiotherapy. 14…”
Section: Discussionmentioning
confidence: 99%